PROSES PELAKSANAAN SOP APLIKASI PELAYANAN TERPADU SATU PINTU (PTSP) DALAM KEGIATAN ADMINISTRASI PADA SUBBAGIAN UMUM DI PENGADILAN TINGGI BANDUNG - Emilia, Elsha; Yusuf, Ramayani; Azizah, Nur; Nurcahya, Said Bambang (LPPM Politeknik Pajajaran ICB Bandung, 2025)
This study aims to examine the implementation of Standard Operating Procedures (SOP) in the One-Stop Integrated Service (PTSP) application for administrative activities at the General Subdivision of Bandung High Court. The research uses a descriptive qualitative method with data collection techniques including interviews, observations, and literature review. The results show that PTSP SOP implementation improves effectiveness, efficiency, transparency, and accountability of administrative processes. However, technical challenges remain, such as internet network instability and limited staff understanding. Overall, PTSP supports the enhancement of public service quality and contributes to more efficient bureaucratic reform.